Educação infantil: a porta de entrada para o ensino-aprendizagem de língua inglesa - Linguevis, Ana Maria (2007)
For a long time both private schools and language institutes have been teaching English for kindergarteners and nowadays we face this phenomenon also in the public schools in the State of Sao Paulo. This research aims to describe and interpret the phenomenon of teachinglearning English for children. The theoretical framework that orients the research is: Theories proposed by Vygotsky (1930/1998;1934/1987;1925/2001), Bakthins concept of language (1929/2004;1979/2003), the role of a foreign language expressed by the Parâmetros Curriculares Nacionais - Língua Estrangeira (Brasil, 1998), the Referencial Curricular Educação Infantil (1998), Escola Tempo Integral (2006), Celani (2001;2003;2004), Freire (1986;1993;1996), Kumaravadivelu (1994;2001), Canagarajah (2002), Claxton (2000), Allwright (2003), and Higgins (2003). This study is based on the Hermeneutic-Phenomenological Approach proposed by van Manen (1990). The results of the interpretations reveal that the phenomenon in focus shows the need of a pedagogical practice of learning-teaching English that includes a vision of language that guides the children towards the ownership of the language (Higgins, 2003) and shows that the structure of the phenomenon in focus consists of one major theme: inquiries